Benturan Kepentingan bagi Konsultan Hukum dalam Kejahatan Pasar Modal - Elvira Fitriyani Pakpahan; Selvia Fransiska Wijaya; Agnes Fortunata; Johny Chang; Helfan Muhammad (Universitas Medan Area, 2019)
This objective of this research is to examine conflicts of interest for legal consultants in capital market crime. The method used in this study is normative juridical analysis with a library approach and using secondary data. The role of legal consultants is very important in the capital market, this is because legal consultants are required to provide legal opinions regarding a company. So, because it has an important role, a legal consultant needs to know the duties and obligations. Beside that, the information from legal opinions will be used by investors in deciding whether to invest their capital or not, because information in the capital market is a factor that causes the fluctuations in the price of securities or shares on the price of securities or shares. Therefore, in each assignment of a legal consultant, it is expected that legal consultants can act independently and impartially and in accordance with the code of ethics, professional standards and applicable regulations. Sanctions will be given to legal consultants who act independently and do not fulfill the code of ethics, professional standards and applicable regulations. The application of sanctions is also related to the role of the Financial Services Authority.